MKK6 is Upregulated in Human Esophageal, Stomach, and Colon Cancers. (14th September 2014) - Parray, Arif Ali; Baba, Rafia Anjum; Bhat, Hina Fayaz; Wani, Lateef; Mokhdomi, Taseem Ahmad; Mushtaq, Umar; Bhat, Sehar Saleem; Kirmani, Deeba; Kuchay, Sanaullah; Wani, Mudassir Maqbool; Khanday, Firdous Ahmad
<x xml:space="preserve">Abstract</x> Expression analysis of MKK6 protein in solid tumors has never been investigated. Here, we report systematic analysis of MKK6 protein in different types of human tumor samples using western blotting and immunofluorescence techniques. We observed significant increase in the expression of MKK6 in Esophageal, Stomach, and Colon cancers as compared to controls. Results were alternately confirmed by Immunofluorescence studies. Upregulation of MKK6 protein is indicative of its role in human cancers and could possibly be used as a novel diagnostic or prognostic marker in these cancers.